2013
DOI: 10.1039/c3lc41309h
|View full text |Cite
|
Sign up to set email alerts
|

Remote detection NMR imaging of gas phase hydrogenation in microfluidic chips

Abstract: The heterogeneous hydrogenation reaction of propene into propane in microreactors is studied by remote detection (RD) nuclear magnetic resonance (NMR). The reactors consist of 36 parallel microchannels (50 × 50 μm(2) cross sections) coated with a platinum catalyst. We show that RD NMR is capable of monitoring reactions with sub-millimeter spatial resolution over a field-of-view of 30 × 8 mm(2) with a steady-state time-of-flight time resolution in the tens of milliseconds range. The method enables the visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…Consequently,t he spins at the exit (bottom)o ft he reactora re observed first and those at the entrance (top) last. [45],a nd the resultingv alue was 600 AE 90 ms. The arrow becomes slightly elongated at longerT OF instances, implyingt hat the flow velocity is slightly smaller in the outer- Figure 5t he right most panel), the signal amplitude is considerably higher in the lower parto ft he chip than in the upperp artd ue to T 1 relaxation.…”
Section: Nmr Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently,t he spins at the exit (bottom)o ft he reactora re observed first and those at the entrance (top) last. [45],a nd the resultingv alue was 600 AE 90 ms. The arrow becomes slightly elongated at longerT OF instances, implyingt hat the flow velocity is slightly smaller in the outer- Figure 5t he right most panel), the signal amplitude is considerably higher in the lower parto ft he chip than in the upperp artd ue to T 1 relaxation.…”
Section: Nmr Characterizationmentioning
confidence: 99%
“…The sensitivity problem is especially difficult when low density gaseous fluids are investigated. [45] The method provides also time-of-flight (TOF)i nformation as the travel time from the encoding region to the detector depends on the initial spatialp osition of the encoded molecule. [36][37][38][39][40][41][42] In this work, the yield of the hydrogenation reaction in the microfluidic chips was determined from 1 HNMR spectra measured by an ultrasensitive microsolenoidw ound around an outlet capillaryw hile the gas mixture was flowing out from the reactor.F urthermore, remote detection (RD) NMR [43,44] was utilized for visualization of the gas flow in the reactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a method using the temperature dependence of chemical shift difference between the two signals of ethylene glycol, well known from high resolution NMR spectroscopy [26], was adapted for temperature measurements within an NMR compatible reactor [27]. Even gas phase reactions were investigated by using hyperpolarization or remote detection techniques [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Further efforts were directed to the development of the concept by employing micro-engineering technologies to produce micro-structured lab-on-a-chip reactors with the catalyst (sputtered Pt) deposited on the inner surface of the channels. [231] It was found that these reactors did not provide PHIP. However, these studies provided a platform for further development of RD NMR for future HP applications, e.g., by using Hadamard encoding to achieve a better chemical resolution.…”
Section: Microfluidic Reactor Imagingmentioning
confidence: 99%